2009
DOI: 10.1002/ijc.24601
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induces chemoresistance in ovarian cancer cells by activation of signal transducer and activator of transcription 3

Abstract: Signal transducer and activator of transcription 3 (STAT3) is activated in a variety of human cancers, including ovarian cancer. The molecular mechanism by which the STAT3 is activated in cancer cells is poorly understood. We observed that human ovarian xenograft tumors (A2780) in mice were severely hypoxic (pO 2 2 mmHg). We further observed that hypoxic exposure significantly increased the phosphorylation of STAT3 (pSTAT3) at the Tyr705 residue in A2780 cell line. The pSTAT3 (Tyr705) level was highly dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
104
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 41 publications
10
104
1
Order By: Relevance
“…Moreover, the reduced effectiveness of conventional chemotherapeutic drugs cisplatin and taxol in eliminating the hypoxic ovarian cancer cells suggests a role for pSTAT3 in cellular resistance to chemotherapy. It has been shown that inhibition of STAT3 followed by treatment with cisplatin or taxol resulted in a significant increase in apoptosis supporting the hypothesis that hypoxia-induced STAT3 activation is responsible for chemoresistance (Selvendiran et al, 2009). According to this evidence the correction of anaemia and the maintenance of adequate Hb levels during cancer chemotherapy should be addressed as a fundamental outcome in the therapeutic strategies of EOC.…”
Section: Inflammation and Possible Therapeutic Implicationsmentioning
confidence: 70%
“…Moreover, the reduced effectiveness of conventional chemotherapeutic drugs cisplatin and taxol in eliminating the hypoxic ovarian cancer cells suggests a role for pSTAT3 in cellular resistance to chemotherapy. It has been shown that inhibition of STAT3 followed by treatment with cisplatin or taxol resulted in a significant increase in apoptosis supporting the hypothesis that hypoxia-induced STAT3 activation is responsible for chemoresistance (Selvendiran et al, 2009). According to this evidence the correction of anaemia and the maintenance of adequate Hb levels during cancer chemotherapy should be addressed as a fundamental outcome in the therapeutic strategies of EOC.…”
Section: Inflammation and Possible Therapeutic Implicationsmentioning
confidence: 70%
“…82 ). Inhibition of the phosphoinositol-3-kinase (PI3K) pathway, nuclear factor kappa-B (NF-κB), cycloxygenase-2 (COX-2), activator protein-1 (AP-1), cjun, Pim-1, and STAT-3 can reverse resistance to cytostatics in hypoxia, implying a role for these pathways in hypoxia-induced drug resistance 10,18,22,23,33,77,83,84 . However, the degree in which they are dependent on functional HIF-1 is uncertain.…”
Section: Other Factors Responsible For Hypoxia-induced Chemoresistancementioning
confidence: 99%
“…In radiotherapy, low oxygen levels prevent the formation of DNA strand breaks induced by radiation, and inhibits repair of DNA damage that induces genetic instability 3,4 . Hypoxia-induced resistance to cisplatin, doxorubicin, etoposide, melphalan, 5-flouoruracil, gemcitabine, and docetaxel has been previously reported in a number of tumor cell types [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . Hypoxia regulates approximately 1% of the genes that play a role in the signaling pathways that control various aspects of tumor progression 24 .…”
Section: Introduction -Hypoxia-induced Chemoresistancementioning
confidence: 99%
“…Hypoxia in solid tumors is not only a major problem for radiation therapy but also leads to resistance against most anticancer drugs (Hockel and Vaupel, 2001;Chan et al, 2007;Selvendiran et al, 2009). Adaptations of cancer cells to hypoxia are critical for the establishment of a primary tumor and its progression to the lethal phenotype (Semenza, 2000) by stimulating HIF-1 and by activating transcription of target genes (Zhong et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen supply to the tumor cells is often diminished because tumor cells in solid tumor grow faster than the endothelial cells that build up the blood vessels (Folkman, 1990). Hypoxia in solid tumors is one of major causes to resistance against most anticancer drugs and, importantly, appears to accelerate malignant progression and increase metastasis (Hockel and Vaupel, 2001;Chan et al, 2007;Selvendiran et al, 2009). Transcription factor, hypoxia-inducible factor alpha (HIF)-1 plays an essential role in the cellular response to changes in oxygen tension (Papandreou et al, 2006).…”
Section: Introductionmentioning
confidence: 99%